12 - Forced into Adulthood: An Exploration of Psycho-Social Dynamics in Child-headed Households - Muyomi, Bernadette (Africa Development, 2021)
Child-headed households are a common family arrangement in the coastal region of Kenya and beyond. These households are mainly precipitated by situations in the lives of parents that force children to take up social roles that are usually reserved for adults. While children have rights just like adults, their well-being is compromised without parents’ involvement in their lives because of missing parental obligations. Children in child-headed households are forced to handle responsibilities that are not appropriate for their developmental age, often denying them a sense of childhood comfort and burdening them emotionally, socially and psychologically. Such children end up with numerous psycho- social challenges, including low self esteem, early marriages, exposure to child labour, prostitution, trafficking and social exclusion, among others. The situation is a vicious cycle, bound to recur since such children also become parents at an early age. This paper uses data from coastal Kenya to show the inevitability of child-headed households and the need to treat such households as part of the larger repertoire of nuclear family set ups in the society.